PELATIHAN TEKNIK STORYTELLING DALAM PUBLIC SPEAKING DI DEPAN KAMERA BAGI SANTRIWATI PONDOK PESANTREN ROOIHATUL JANNAH SUKOHARJO - Dani Kurniawan (Universitas Muhammadiyah Klaten, 2026)
Abstract The development of digital media requires every individual, including female Islamic boarding school students, to possess effective communication skills, particularly when speaking in front of a camera. However, many female students still struggle to convey messages in a coherent, engaging, and confident manner. Therefore, this community service activity aims to enhance the knowledge and skills of female students in applying storytelling techniques to public speaking in front of a camera. The activity was held at the Rooihatul Jannah Islamic Boarding School with 33 participants, 31 of whom completed the entire program. The implementation methods included presenting material on public speaking, storytelling techniques, and techniques for speaking on camera, followed by hands-on practice and evaluation through participant testimonial sessions. The results of the activity showed that the training went well and received positive feedback. Participant attendance reached 93.94%, while the evaluation of the material delivery showed that 72% of participants rated it as good, 18% as fair, and 10% as poor. In addition, the storytelling techniques module was perceived as the most beneficial by participants (31%), followed by building confidence in front of the camera (24%), camera operation (17%), delivering engaging messages (16%), and crafting storytelling scripts (12%). Overall, this program successfully improved the participants’ understanding of storytelling techniques, boosted their confidence in speaking in front of the camera, and enhanced their ability to convey messages more effectively. It is hoped that this training will equip the female students with the skills they need for presentations, da’wah, and communication through digital media.Keyword: storytelling, public speaking, digital communication, speaking on camera, female Islamic boarding school students.